QuickBooks 2018 all-in-one for dummies - Nelson, Stephen L., 1959- (--For dummies., 2018)
The easy way to manage business finances QuickBooks is known for helping their users effectively handle their financial and business management tasks, and QuickBooks 2018 All-in-One For Dummies is the go-to guide for anyone looking to gain insight into the latest version of the software. It gets you up to speed on the key features of QuickBooks and small business accounting and makes managing finances a breeze. This book will help you learn all the skills you need to know, like how to invoice customers, pay vendors, manage cash and bank accounts, use activity-based costing, and write a business plan. Written by highly qualified CPA Stephen L. Nelson, this detailed reference combines eight mini-books into one complete resource. Small business finances can be complicated, but QuickBooks 2018 is a valuable tool for getting them right--and this guide makes it easier. Troubleshoot and protect your financial data Utilize Cloud storage and access your information from a smartphone Plan and set up a QuickBooks system Make sense of double-entry bookkeeping Handle your financial and business management tasks more effectively QuickBooks 2018 All-in-One For Dummies is a helpful resource for getting started with QuickBooks 2018, and a reference guide that will provide insight and answers to experienced users as well.